The Impact of Using Balanced Scorecard on Employee’s Performance: A Field Study in King Faisal Specialty Hospital in Jeddah province - Al Jahdali, Aisha Jameaa; Ahmed, Alaa ElDin Mohamed Khalaf (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to examine the use of balanced scorecard (BSC) in government hospitals, as well as its impacts on employee’s performance. In order to achieve these goals a field study was conducted in King Faisal Specialty Hospital (KFSH) in Jeddah province, which had announced in 2015 its implementation of BSC as a performance management tool. The analytical descriptive method was used by the researchers, and a questionnaire- based survey was conducted to obtain necessary data from targeted population including all workers in all levels in KFSH (physicians, nursing, technicians and administrative staff). (245) out of (340) questionnaires were retrieved and were valid to be analyzed. The study showed an existence of significant relationship between adaptation of BSC and employees’ performance since it’s allows hospital to manage performance in all aspects. The research also found that there was a variety degree for BSC perspectives implementation by KFSH where customer’s perspective was the highest and financial perspective was the lowest–due to the nonprofit purpose of KFSH and its focusing on curing certain diseases, The study also showed an existence of significant relationship between adaptation of BSC and employees’ performance, and statistically significant differences between the means of sample subjects’ responses according to the variables of their demographic characteristics. In the light of the results the study recommended a better investment in the human resources as they are the major factor that leads to improve the other aspects